Establecimiento y manejo de cruzamientos y viveros de crianza - Rodríguez, R. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
Three basic hybridization techniques used in crossbreeding are briefly described, namely: (1) emasculation with covered stigma, (2) emasculation with naked stigma, and (3) without emasculation. Their resp. advantages and disadvantages are compared. Hybridization is affected by external plant factors (humidity, temp., air, light), by internal factors (days to flowering, competition, and adaptation), and by practical aspects of the technique (stage of floral buds, no. of crosses/plant, no. of buds/raceme, and use of hormones). Recommendations are given on location of the trials, hour, planting times, technique used, and identification of materials. Harvested hybrid pods are used to establish the F1 breeding nursery. (CIAT)